The difference in serum alkaline phosphatase levels between girls with precocious puberty and those with normal puberty - Hye Jeong Jwa; Soo In Yang; Han Hyuk Lim (Korean Society of Pediatric Endocrinology, 2013)
PurposeSerum alkaline phosphatase (ALP) level is the most valid marker of bone formation. Precocious puberty (PP) in girls is characterized by early growth acceleration. The aim of this study was to determine whether serum ALP levels differ between girls with PP and those with normal puberty, and whether ALP level varies with age or Tanner stage.MethodsThis retrospective study included girls with PP (n=61) and normal puberty (n=71) who visited the outpatient clinic at Department of Pediatrics, Chungnam National University Hospital from March 2010 to August 2011. We obtained age, height, parental height, weight, bone age, Tanner stage, and concentrations of luteinizing hormone, follicular-stimulating hormone, estradiol, ALP, and insulin-like growth factor-1 (IGF-1) from the participants' medical records.ResultsAge and predicted adult height were significantly lower in girls with PP than in those with normal puberty. The height standard deviation score (SDS), weight SDS, body mass index, midparental height, bone age, and IGF-1 level were higher in girls with PP than in those with normal puberty. ALP level was significantly higher in 5- to 8-year-old girls with PP than in age-matched girls with normal puberty. The mean ALP levels were higher in girls with PP than bone age-matched girls with normal puberty (P=0.0003)ConclusionSerum ALP level showed the significance differences between girls with PP and those with normal puberty. The reasons for and the mechanisms underlying this elevation in serum ALP level in girls with PP should be investigated further.